2022
DOI: 10.1088/1402-4896/ac7ebc
|View full text |Cite
|
Sign up to set email alerts
|

Fractional order mathematical model of monkeypox transmission dynamics

Abstract: In this paper, we present a deterministic mathematical model of monkeypox virus by using both classical and fractional-order differential equations. The model includes all of the possible interactions that contribute to disease spread in the population. We investigate the model’s stability results in the disease-free case when R 0 < 1. When R 0 < 1, we show that the model is stable, otherwise it is unstable. To obtain the best fit that describes the dynamics of this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 36 publications
(38 reference statements)
0
44
0
Order By: Relevance
“…The researchers analyzed the parameters of the model and found that the human-to-human contact rate was the most sensitive parameter for monkeypox virus transmission. Shortly before, the team presented a deterministic mathematical model using classical and fractional-order differential equations [ 16 ]. Using nonlinear least squares, the researchers fitted new cases of monkeypox in Nigeria from January 2019 to December 2019.…”
Section: Updated Epidemiology Of Monkeypoxmentioning
confidence: 99%
“…The researchers analyzed the parameters of the model and found that the human-to-human contact rate was the most sensitive parameter for monkeypox virus transmission. Shortly before, the team presented a deterministic mathematical model using classical and fractional-order differential equations [ 16 ]. Using nonlinear least squares, the researchers fitted new cases of monkeypox in Nigeria from January 2019 to December 2019.…”
Section: Updated Epidemiology Of Monkeypoxmentioning
confidence: 99%
“…There have been few studies on the disease's transmission in the past [ [21] , [22] , [23] , [24] , [25] ]. However, mathematical models have been used to study the transmission of diseases such as COVID-19 [ [34] , [35] , [36] ] and diseases belonging to the family Poxviridae such as smallpox [ [26] , [27] , [28] ], chickenpox [ 29 , 30 ] and cowpox [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional derivatives have been proposed for application in mathematical models to understand viral infections [ [1] , [2] , [3] , [4] , [5] , [6] , 9 , 11 , 33 ]. Because they have more degrees of freedom than integer-order models, fractional-order models are more precise and trustworthy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many decades, mathematical models have been formulated and examined to study how various epidemic diseases are controlled and spread. For example, see [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] and the references therein. To better understand the dynamics of co-infection diseases, some studies have been developed (see [21] , [35] , [36] , [4] , [37] ).…”
Section: Introductionmentioning
confidence: 99%